The Addictive Game toward Children with ADHD - Luqyana Dhiya Amira; Abdul Huda; Rizqi Fajar Pradipta (Journal of ICSAR, 2021)
Games are a technology that is constantly evolving and very attractive to many people. High game usage will continue because of the increased quality of technology, especially smartphones. Addictive game is the impact of the use of games that are not controlled. Everyone has the possibility to addictive games, including children with special needs. For example, ADHD is very attached to his favorite object. This study aims to determine the addictive characteristics of games on ADHD, the impacts and treatment by people around the child. This study uses a qualitative research design with a single case study type. Qualitative with this type of single case study conducted because of the uniqueness of the things to be studied and will be examined more deeply. The research subjects are children with ADHD, seven years old, who are addicted to games. Data collection was carried out through three techniques, interviews, observation, and documentation. The results showed that children with ADHD are more vulnerable to addictive games and have a considerable risk than children in general. It can be seen in the characteristics and addictive impacts of games on ADHD.